Hierarchic Branch Morphology, Needle Chlorophyll Content, and Needle and Branch Non-Structural Carbohydrate Concentrations (NSCs) Imply Young Pinus koraiensis Trees Exhibit Diverse Responses Under Different Light Conditions - Bei Li; Wenkai Li; Sudipta Saha; Xiao Ma; Yang Liu; Haibo Wu; Peng Zhang; Hailong Shen (Horticulturae)
Research on young trees’ adaptation to shade has predominantly focused on leaf-level responses, overlooking critical structural and functional adaptations in branch systems. In this study, we address this gap by investigating hierarchical branch morphology–physiology integration in 20-year-old Pinus koraiensis specimens across four distinct light conditions classified by photosynthetic photon flux density (PPFD): three in the understory (low light, LL: 0–25 μmol/m2/s; moderate light, ML: 25–50 μmol/m2/s; and high levels of light, HL: 50–100 μmol/m2/s) and one under full light as a control (FL: 1300–1700 μmol/m2/s). We measured branch base diameter, length, and angle as well as chlorophyll and NSCs content in branches and needles. Branch base diameter and length were more than 1.5-fold higher in the FL Korean pine trees compared to the understory-grown ones, while the branching angle and ratio in the LL Korean pine trees were more than two times greater than those in the FL trees. As light levels increased, Chlorophyll a and b and total chlorophyll (Chla, Chlb, and Chl) concentrations in the needles all significantly decreased. Starch, glucose, and NSC (Starch + Soluble Sugars) concentrations in both needles and branches were the highest in the trees under FL and lowest under ML (except for soluble sugars in branches). Understory young P. koraiensis trees morphologically and physiologically adapt to limited light conditions, growing to be more horizontal, synthesizing more chlorophyll in needles, and attempting to increase their light-foraging ability. We recommend gradually expanding growing spaces to increase light availability for 20-year-old Korean pine trees grown under canopy level.